Politics and reformations : communities, polities, nations, and empires : essays in honor of Thomas A. Brady, Jr. - Brady, Thomas A.; Ocker, Christopher (Studies in medieval and Reformation traditions, 2007)
These twenty-six essays examine urban, rural, national, and imperial histories in Early Modern Europe and abroad, and politics in Reformation Switzerland, Burgundy, Germany, and the Netherlands.